Analysis of stability and Hopf bifurcation for HIV-1 dynamics with PI and three intracellular delays. (February 2016) - Monica, C.; Pitchaimani, M.
Abstract: Mathematical model for the effects of protease inhibitor on the dynamics of HIV-1 infection model with three delays is proposed and analyzed. Some analytical results on the global stability of viral free steady state and infected steady state are obtained. The stability/instability of the positive steady state and associated Hopf bifurcation are investigated by analyzing the characteristic equations.